2021
DOI: 10.1111/and.14286
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 is not found in human semen during mild COVID‐19 acute stage

Abstract: The aim of this study was to verify the presence of SARS‐CoV‐2 in the seminal sample of men during the acute phase of COVID‐19. A prospective study was performed with inclusion of twenty‐two men diagnosed with COVID‐19 through RT‐PCR from pharyngeal smear samples and who were in the acute phase of infection. These men were evaluated regarding medical history and physical examination. Furthermore, seminal samples of each men were collected 7, 14 and 21 days after the infection was confirmed. The sample were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…There is also a hypothesis that states testicular injury and inflammatory infiltration viral orchitis can lead to the secretion of COVID-19 in semen [ 9 , 6 ]. Our results are similar to Song et al [ 9 ], Omolaoye et al [ 12 ], Pan et al [ 8 ], and Fraietta et al [ 13 ] with negative findings for COV-2 in semen samples. Conversely, Li et al reported positive sample COV-2 status in some patients [ 6 ].…”
Section: Discussionsupporting
confidence: 92%
“…There is also a hypothesis that states testicular injury and inflammatory infiltration viral orchitis can lead to the secretion of COVID-19 in semen [ 9 , 6 ]. Our results are similar to Song et al [ 9 ], Omolaoye et al [ 12 ], Pan et al [ 8 ], and Fraietta et al [ 13 ] with negative findings for COV-2 in semen samples. Conversely, Li et al reported positive sample COV-2 status in some patients [ 6 ].…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have suggested the absence of SARS-CoV-2 RNA in semen samples of asymptomatic COVID-19-positive men or those suffering or recovering from mild COVID-19, even though they were still in the acute phase and positive for the virus in the nasopharyngeal swab ( Holtmann et al , 2020 ; Rawlings et al , 2020 ; Best et al , 2021 ; Burke et al , 2021 ; Guo et al. , 2021a ; Gupta et al , 2021 ; Ma et al , 2021 ; Paoli et al , 2021a ; Ruan et al , 2021 ; Scroppo et al , 2021 ; SharMa et al , 2021 ; Temiz et al , 2021 ; Donders et al , 2022 ; Fraietta et al , 2022 ; Huang et al , 2022b ; Pavone et al , 2022 ). Other authors reported the presence of SARS-CoV-2 in the semen and in the seminal plasma fraction (by PCR testing) in the acute phase and after recovery after mild and moderate COVID-19 in a limited percentage of patients, respectively, in 4/15, 1/6, 1/31, 1/19 and 6/38 cases ( Li et al , 2020a ; Delaroche et al , 2021 ; Machado et al , 2021 ; Purpura et al , 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…The semen of 428 patients of 19 articles was analyzed for possible presence of SARS-CoV-2 ( 22 , 24 , 34 , 35 , 37 , 38 , 41 , 47 - 50 , 54 57 , 59 , 60 - 62 ). Patients included had different severity levels of COVID-19 (from asymptomatic to ICU patients) and semen samples were collected in different periods of the disease.…”
Section: Resultsmentioning
confidence: 99%